The Effect of Price, Quality of Service, and Quality of Service on Customer Satisfaction at Cafe Ranu Raseyan Rantau Prapat - Risa Astari; Elida Florentina Sinaga Simanjorang; Rizky Syahputra (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the effect of price (X1), food quality (X2) and service quality on consumer satisfaction (Y) at Ranu Raseyan Cafe. This type of research is quantitative research. The population used in this study were Ranu Raseyan Cafe customers who were cafe visitors. The sample consists of 100 samples of respondents. The analysis technique used is multiple linear regression. The results showed that (1) the price variable (X1) had a positive and significant effect on consumer satisfaction with the value of t count > t table, namely 3.789 > 1.661. (2) The food quality variable (X2) has a positive and significant effect on consumer satisfaction with the value of t count > t table, namely 2,742 > 1,661. (3) The service quality variable (X3) has a positive and significant effect on customer satisfaction with the value of t count > t table, namely 2.149 > 1.661. (4) Variables of price (X1), quality of dishes (X2), and quality of service (X3) have a positive and significant effect on consumer satisfaction (Y) simultaneously with the calculated F value > F table that is 54,650 > 2,699 . The R2 coefficient value is 0.631, which means price (X1), quality of food (X2), and quality of service (X3) affect customer satisfaction by 61.9%, while 38.1% is influenced by others.